Parvalbumin interneuron deficiency in the prefrontal and motor cortices of spontaneously hypertensive rats: an attention-deficit hyperactivity disorder animal model insight - Bogdańska-Chomczyk, Ewelina; Równiak, Maciej; Huang, Andrew Chih-Wei; Kozłowska, Anna (Frontiers in Psychiatry, 2024)
Background Attention deficit hyperactivity disorder (ADHD) is characterized by impairments in developmental–behavioral inhibition, resulting in impulsivity and hyperactivity. Recent research has underscored cortical inhibition deficiencies in ADHD via the gamma-aminobutyric acid (GABA)ergic system, which is crucial for maintaining excitatory–inhibitory balance in the brain. This study explored postnatal changes in parvalbumin (PV) immunoreactivity, indicating GABAergic interneuron types, in the prefrontal (PFC) and motor (MC) cortices of spontaneously hypertensive rats (SHRs), an ADHD animal model. Methods Examining PV- positive (PV+) cells associated with dopamine D2 receptors (D2) and the impact of dopamine on GABA synthesis, we also investigated changes in the immunoreactivity of D2 and tyrosine hydroxylase (TH). Brain sections from 4- to 10-week-old SHRs and Wistar Kyoto rats (WKYs) were immunohistochemically analyzed, comparing PV+, D2+ cells, and TH+ fiber densities across age-matched SHRs and WKYs in specific PFC/MC regions. Results The results revealed significantly reduced PV+ cell density in SHRs: prelimbic ( 20% less), anterior cingulate ( 15% less), primary ( 15% less), and secondary motor ( 17% less) cortices. PV+ deficits coincided with the upregulation of D2 in prepubertal SHRs and the downregulation of TH predominantly in pubertal/postpubertal SHRs. Conclusion Reduced PV+ cells in various PFC regions could contribute to inattention/behavioral alterations in ADHD, while MC deficits could manifest as motor hyperactivity. D2 upregulation and TH deficits may impact GABA synthesis, exacerbating behavioral deficits in ADHD. These findings not only shed new light on ADHD pathophysiology but also pave the way for future research endeavors.